Profil Kemampuan Berpikir Kritis Materi Ekosistem di SMP Yapis Manokwari dengan Menggunakan Model Rasch - Irmansyah Karoror; Tri Jalmo (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine the ability of students in solving critical thinking questions. There are 20 multiple choice questions as an instrument of critical thinking questions. The test was carried out in class VII SMP Yapis Manokwari which consisted of 23 students. This research is a descriptive study using the Rasch model with winstep software. The results showed that the average score of students in solving critical thinking questions reached 57%. The Rasch model shows that students 23, 04, and 21 have high intelligence, while students 05, 08, 03, 10, 17, 01, 15, 19, 11, and 18 have the lowest abilities. The results showed that the ability of students to solve critical thinking questions was still in the low category. This can be used as an evaluation description for teachers to improve students' critical thinking skills